ANALISIS BAURAN PEMASARAN TERHADAP KEPUTUSAN KONSUMEN MEMBELI KUE TALAM DURIAN DI RUMAH KUE VIERA JALAN MELATI KOTA PEKANBARU - Ananda Pratama; Ermy Tetty; Shorea Khaswarina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
The purpose of this research are : 1) Analyze the marketing mix that affects consumers ' decision to buy Talam Durian cakes at the Viera Cake House on Melati street Pekanbaru city 2) To analyze the relationship between marketing mix to consumer decision to buy Talam Durian at the Viera Cake House on  Melati street Pekanbaru city. The data analysis used is the marketing mix analysis. Consumer decision in making the purchase of Talam Durian cake by 7 (Seven) variable marketing mix IE product, price, location, promotion, person, physical means and process. Products with the category of "influential", the price with the category "influential", the place with the category "Quite influential", the promotion with the category "influential", People with the category "influential", physical means with the category of "influential" and the process with "influential" category. Overall the marketing mix variable is in the "influential" category of the consumer purchase decision at Rumah Kue Viera. Correlation analysis Rank Spearman that indicates the relationship between the marketing mix to the consumer's decision is positive and very strong and significant ( x = 0,01). The correlation coefficient of marketing mix marked positive (+), meaning the relationship of marketing mix with consumer decision is in the direction of so if the marketing mix increases then the consumer's decision will also increase.Keywords : Consumer's Decision, Marketing Mix